What Are Predictors for Persistence in Childhood Stuttering? - Walsh, Bridget; Usler, Evan; Bostian, Anna; Mohan, Ranjini; Gerwin, Katelyn Lippitt; Brown, Barbara; Weber, Christine; Smith, Anne (Seminars in Speech and Language, 2018)
Over the past 10 years, we (the Purdue Stuttering Project) have implemented longitudinal studies to examine factors related to persistence and recovery in early childhood stuttering. Stuttering develops essentially as an impairment in speech sensorimotor processes that is strongly influenced by dynamic interactions among motor, language, and emotional domains. Our work has assessed physiological, behavioral, and clinical features of stuttering within the motor, linguistic, and emotional domains. We describe the results of studies in which measures collected when the child was 4 to 5 years old are related to eventual stuttering status. We provide supplemental evidence of the role of known predictive factors (e.g., sex and family history of persistent stuttering). In addition, we present new evidence that early delays in basic speech motor processes (especially in boys), poor performance on a nonword repetition test, stuttering severity at the age of 4 to 5 years, and delayed or atypical functioning in central nervous system language processing networks are predictive of persistent stuttering.
Keywords: Stuttering; speech motor control; persistence; recovery; children; language; emotion; fNIRS; ERP